Fitrah-Based Meaningful Learning in Islamic Religious Education: A Case Study of Life Skills Development at Bintang Madani High School - Ulfah Salwa Hasibuan; Munawar Rahmat; Saepul Anwar (Mimbar Agama Budaya, 2026)
Islamic Religious Education (PAI) is often criticized for emphasizing memorization and normative understanding rather than helping students develop practical life skills needed in contemporary society. This qualitative single-case study explores the implementation of fitrah-based Meaningful Learning at Bintang Madani High School in cultivating students’ life skills, particularly autonomous motivation, adaptability, and reflective self-awareness. Data were collected from one PAI teacher and four students through classroom observations, semi-structured interviews, and document analysis, and were analyzed using a hybrid thematic coding approach supported by NVivo 15 software. The findings reveal three main features of the learning model: (1) the contextualization of theological content through contemporary issues relevant to students’ lives, (2) the integration of domestic life skills and industrial internship experiences, and (3) the use of restorative discipline and reflective learning programs. These practices encourage students to engage with religious learning more meaningfully, adapt to real-life social and vocational contexts, and develop greater awareness of their own beliefs, actions, and responsibilities. The study suggests that the integration of fitrah-based education and Meaningful Learning provides a promising approach for making PAI more relevant to students’ everyday experiences. The findings also offer practical insights for educators and curriculum developers seeking to strengthen the connection between religious learning and life-skill development.